Youth Perspectives on Social Insurance in Egypt: Qualitative Insights on the Gap between Legal and Effective Coverage. (November 2016) - Sieverding, Maia
Abstract : A gap between legal and effective coverage rates is a common challenge facing social insurance systems in Low‐ and Middle‐Income Countries. This article draws on an exploratory qualitative study with youth in Egypt to examine how labour market dynamics and worker preferences contribute to this gap. Labour market factors, particularly instability of employment and job mobility, were found to reduce the perceived value of social insurance. Poor understanding of how social insurance works was another contributing factor. However, youth displayed a high level of trust in the public social insurance system and saw pensions as valuable in the abstract. In combination with awareness promotion, eliminating penalties to discontinuous labour force participation could make social insurance more attractive to youth.